1995
DOI: 10.1093/gerona/50a.1.m35
|View full text |Cite
|
Sign up to set email alerts
|

Case Mix Controlled Service Use and Expenditures in the Social/Healt Maintenance Organization Demonstration

Abstract: Overall plan losses and higher expenditures among a number of case mix groups suggest a need for refinement of S/HMO operations--especially in case management relationships to medical care and in the selection of "high risk" cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…There is, however, general agreement that the Social HMO model fell short of expectations during the initial 3-year demonstration phase (1986-1989) (1). Nevertheless, the sum total of findings suggests several outcomes in a positive direction: 1) the majority of enrollees expressed satisfaction with the program, and family caregivers found its long-term care features very helpful (18,19); 2) while no overall cost savings were observed, one of the sites provided more services to the most impaired group for less cost than the traditional fee-for-service sector (20,21); 3) although the sites did not show consistent positive effects with respect to institutional utilization, one of the Social HMOs found that its elderly enrollees spent 25 percent fewer days in nursing homes as compared to elderly members of conventional, medically-oriented HMOs (22)(23)(24); and 4) overall, the demonstration established the feasibility of integrating responsibilities for the financing and delivery of acute and long-term care in one organizational entity, though this proved to be a complex undertaking (1).…”
Section: Social Health Maintenance Organization (Social Hmo)mentioning
confidence: 99%
“…There is, however, general agreement that the Social HMO model fell short of expectations during the initial 3-year demonstration phase (1986-1989) (1). Nevertheless, the sum total of findings suggests several outcomes in a positive direction: 1) the majority of enrollees expressed satisfaction with the program, and family caregivers found its long-term care features very helpful (18,19); 2) while no overall cost savings were observed, one of the sites provided more services to the most impaired group for less cost than the traditional fee-for-service sector (20,21); 3) although the sites did not show consistent positive effects with respect to institutional utilization, one of the Social HMOs found that its elderly enrollees spent 25 percent fewer days in nursing homes as compared to elderly members of conventional, medically-oriented HMOs (22)(23)(24); and 4) overall, the demonstration established the feasibility of integrating responsibilities for the financing and delivery of acute and long-term care in one organizational entity, though this proved to be a complex undertaking (1).…”
Section: Social Health Maintenance Organization (Social Hmo)mentioning
confidence: 99%
“…The federal evaluation failed to evaluate the effect of CC and service coordination on nursing home use, Medicaid expenditures, or functional status. Rather, the core evaluation studies of outcomes used a synthetic case mix grouping method that did not pay attention to who actually was eligible for or used the benefit (Newcomer, Manton et al, 1995), and there were additional methodological shortcomings on these studies (Leutz, Greenlick et al, 1994). One evaluation study did study outcomes for those targeted for expanded care and found that informal care for frail Social HMO members was maintained better than such care for the fee-for-service frail.…”
Section: Case Management Utilization and Costs In The Social Hmomentioning
confidence: 99%
“…The first social health maintenance organisations gave disappointing results,21 but a second generation is more ambitious, attempting to identify clinical problems early and to intervene efficiently with expert interdisciplinary teams 22…”
Section: Innovations In Chronic Carementioning
confidence: 99%